Knowledge and thresholds for palliative care and surgery among healthcare providers caring for adults with serious illness - Juan, Darryl Wen Kai; Ng, Irene Ai Ting; Wong, Louis Choon Kit; Fong, Wei Jing; Lee, Piea Peng; Lie, Sui An; Zhou, Jamie Xuelian; Cai, Mingzhe; Ong, Johnny Chin-Ann; Seo, Jane Chin Jin; Chia, Claramae Shulyn; Wong, Jolene Si Min (Frontiers in Medicine, 2024)
Introduction Timely palliative care and surgical interventions improve symptoms, health-related quality of life (HRQoL), and reduce medical cost for seriously ill adults at end of life (EOL). However, there is still poor delivery and underutilization of these palliative services. We hypothesize that the sub-optimal delivery is due to limited understanding among healthcare providers. Methods A nationwide cross-sectional online survey was conducted among primary and tertiary healthcare providers. The survey assessed challenges faced, palliative education, confidence in managing palliative patients, and knowledge on palliative surgery. Overall palliative care awareness and knowledge was assessed using a 6-point score. Likelihood of considering various palliative interventions at EOL was also determined using a threshold score (higher score = higher threshold). Results There were 145 healthcare providers who completed the survey (81.9% response rate); majority reported significant challenges in providing various aspects of palliative care: 57% (n = 82) in the provision of emotional support. Sixty-nine percent (n = 97) in managing social issues, and 71% (n = 103) in managing family expectations. Most expressed inadequate palliative care training in both under-graduate and post-graduate training and lack confidence in managing EOL issues. Up to 57% had misconceptions regarding potential benefits, morbidity and mortality after palliative surgery. In general, most providers had high thresholds for Intensive Care Unit admissions and palliative surgery, and were more likely to recommend endoscopic or interventional radiology procedures at EOL. Conclusion Healthcare providers in Singapore have poor knowledge and misconceptions about palliative care and surgery. Improving awareness and education among those caring for seriously ill adults is essential.